Penelitian Arkeologi Indonesia Pasca UU Nomor 5 Tahun 1992 - Bugie Kusumohartono (Berkala Arkeologi, 1994)
Until the middle of the last decade, archaeological research was still dominated by previous models of foreign scholar thinking. This thinking model is characterized by an orientation (only) on the relics of the past being studied. In this model the researchers depart from the legacy of the past, which through classification and analysis work will arrive at an interpretation of the role (meaning, function, technology) of the object in question in the past. In fact, often the results of these studies only stop at the level of classification and analysis, without any interpretation.